METHODOLOGY FOR DEVELOPING COMPLEX DECISION-MAKING SKILLS IN A DIGITAL ENVIRONMENT - Muxlisa Xojiyeva Sultonovna (American Journals, 2025)
This study presents a systematic methodology for developing complex decision-making skills in a digital environment. Emphasizing the integration of modern information technologies, the approach aims to enhance analytical thinking, problem-solving abilities, and effective decision-making in dynamic digital contexts. The methodology combines theoretical frameworks with practical applications to support learners and professionals in acquiring high-level cognitive and strategic competencies.
Keywords: Complex decision-making, digital environment, analytical skills, problem-solving, information technologies, methodology.